Possibility of Piezoelectric Sensor to Monitor Onshore Pipeline in Real Time Monitoring - Nurhadi Siswantoro; Aydin Doğan; Dwi Priyanta; Muhammad Badrus Zaman; Semin Semin (International Journal of Marine Engineering Innovation and Research, 2019)
Transportation oil and gas mostly used pipelines transportation. The condition of a pipeline must be continually monitored to ensure that defects do not cause it to fail and operate optimally. Pipeline has the possibility to experience defects during operations such as general corrosion, fatigue, crack, and others. Defects that occur in the pipeline during operation have serious consequences including loss of property, personal injury, or even loss of lives and serious ecological pollution. Awareness of the importance of conducting pipeline monitoring and safety issues for workers and residents around the pipeline site, emphasizes the importance of developing a technology for conducting pipeline monitoring activities in real time. The new technology for detecting metal defects is by using piezoelectric material. Based on laboratory scale, piezoelectric sensor can be applied to monitor pipeline defect. However, it is necessary challenges to scaling up in real application are following: (1) financial investment, (2) human behavior surrounding pipeline area, (3) receiving signal in long distance, (4) protection of piezoelectric sensor, (5) combination survey for future development.